Deep MCL injury cases with arthroscopic findings of hypermobile medial meniscus: A report of six cases of arthroscopic meniscal suture repair - Miyu Inagawa; Takaki Sanada; Hiroshi Iwaso (Elsevier, 2020)
MRI did not detect any abnormality in the medial meniscus besides high-intensity changes at the meniscofemoral portion of the deep medial collateral ligament. Although pure valgus stress test proved no medial joint widening at 0° and 30°, when an examiner applied knee valgus and tibial external rotation force, the patient experienced pain in the anteromedial knee joint that coincided with their refractory symptoms in individual specific activity. Arthroscopy investigation confirmed that the anterior to middle segment of the medial meniscus had excessively slid into the central direction by a probe-drawing manoeuvre; synchronous meniscal movement in the valgus and external rotation test was also observed. After arthroscopic meniscal suture to the lesion had suppressed the abnormal meniscal movement, the patients' refractory anteromedial symptoms disappeared immediately. From their common history of medial collateral injury and the high intensity at the deep medial collateral ligament, we assumed that chronic deep medial collateral ligament impairment sustained the hypermobility of the medial meniscus. Arthroscopic confirmation of hypermobility led to definitive treatment of a simple meniscal suture. Painful deep MCL injuries with hypermobile medial arthroscopic findings are not a rare phenomenon as previously assumed; however, surgeons often fail to recognize its latent clinical features.